Investigation of helmet use behavior of motorcyclists and effectiveness of enforcement campaign using CART approach. (October 2019) - Adnan, Muhammad; Gazder, Uneb
Abstract: Use of the helmet is beneficial in reducing the severity of injuries and avoiding fatalities for motorcyclists, therefore, legislation exists in almost all countries. In practice, the situation is different regarding the helmet use, especially in the developing countries. This paper investigates the helmet use behavior of motorcyclists in Karachi, Pakistan. It determines the significant factors affecting the helmet use in Karachi (Pakistan) and recommending effective campaign measures to promote helmet use. It is vital in relation to the exponential growth of motorcycle users and poor enforcement of traffic rules. Repeated cross-sectional data collected before (n = 226) and after (n = 277) the helmet use enforcement campaign is analyzed using univariate and non-parametric classification and regression tree (CART) techniques. A significant number of motorcyclists do not hold a driving license and CART analysis highlighted the significance of this variable along with exposure to the road environment (measured as daily usage of motorcycle) to explain helmet use. Campaign effects are found temporary, therefore, serious efforts are required to design coherent and structured awareness and enforcement programs. Highlights: Helmet use for motorcyclists using repeated X-sectional survey is analyzed using CART and univariate approaches. The data is collected from Karachi, Pakistan before and after the enforcement campaign. Holding a motorcycle driving license, age and number of daily trips are found to have an effect on helmet use. Effectiveness of an enforcement campaign is determined and some directions for their better design are discussed.